Reliability of intra- and inter-rater palpation discrepancy and estimation of its effects on joint angle measurements. - Moriguchi CS; Carnaz L; Silva LCC; Salasar LE; Carregaro RL; Sato TO; Coury HJC (Manual Therapy, 2009)
This study presents data on the intra- and inter-rater reliability of palpation on normal and overweight subjects and shows the influence of palpation discrepancy on angular variability for a collected data set, using computer simulation. Thirty healthy males were recruited. Two physiotherapists identified 12 anatomical landmarks that enabled measurement of eight joint angles. Palpation discrepancy was determined by photographic recordings under ultraviolet light. Angular discrepancies were determined from photos of the subject's orthostatic posture. A computer simulation was developed to predict expected angular variation according to observed palpation discrepancy. The results showed that the inter-rater reliability was lower than the intra-rater reliability for both palpation and angle measurements. Palpation of the greater trochanter (GT), anterior superior iliac spine (ASIS), seventh cervical vertebra (C7) and femoral epicondyle (FE) showed larger discrepancies. The overweight group presented a significant difference in palpation discrepancy for ASIS (P<0.03). Angular variations were associated with palpation discrepancies for trunk flexion (TF), hip flexion (HF) and pelvic inclination (PI). Therefore, measurements should be performed by a single rater, rather than by different raters, if reliable angular measurements are intended. Specific anatomical landmarks require careful identification. Simulation was useful for providing estimates of variations due to palpation discrepancy.